(untitled) (Journal of Pakistan Orthopaedic Association, 2022)
Objective: To determine the outcome of Ponseti technique of manipulation and serial casting for idiopathic clubfoot in terms of correction achieved as per improvement in Pirani scoring. Methods: This descriptive study was conducted in Orthopaedic department Nishtar Medical University Hospital Multan from 25th January 2019 to 25th January 2021. All children of below one year age with idiopathic clubfoot fulfilling the inclusion criteria were treated with Ponseti method of manipulation and serial casting on weekly basis. Pirani score was used to assess foot deformity before and after casting and interpreted as excellent outcome(0 and 1 score),good outcome(1.5 and 2.5 score) and poor outcome(?3 score).The pre and post casting Pirani score was compared and P value was calculated with paired t-test. P value< 0.05 was considered significant. Results: In this study 100 children with idiopathic club feet were enrolled but 90 children completed the study. Bilateral club feet was present in 45(50%) children and unilateral in 45(50%) children. The total feet treated were 135. The mean age was 45.31±61.87 days. Male children were 53 (58.9%) and female 37 (41.1%). The average number of casts were 5.37±1.80. Tendo Achilles tenotomy was carried out in 73 (81.1%) children. The mean pre casting Pirani score of the right foot was 4.88±1 and post casting 0.13±0.44(p < 0.05) The mean pre casting Pirani score of the left foot was 5.02±1.19 and improvement was noticed with post casting Pirani score of 0.8±0.20(p<0.05).Overall excellent outcome was documented in 110(81.48%) feet and good outcome in 25(18.51%) feet. Conclusion: The Ponseti technique of manipulation and casting was very effective in correcting the club foot deformity as indicated by significant improvement in Pirani scoring and excellent outcome in majority of our patients.